Durably reducing partisan animosity through multiple scalable treatments - Matthew E. K. Hall; Brittany C. Solomon; Jan G. Voelkel; Michael N. Stagnaro; James Y. Chu; Robb Willer (Proceedings of the National Academy of Sciences, 2025)
Recent research has identified several effective strategies for reducing Americans’ animosity toward supporters of opposing political parties. However, whether these strategies can durably reduce partisan animosity in a scalable manner and in everyday life remains unclear. We bridge the gap between prior research and useful application by assessing whether exposure to multiple, scalable treatments that portray inparty and outparty members interacting positively, receiving accurate information about one another’s views, and learning about cross-party similarities can a) durably shift partisans’ sentiments and b) influence partisans’ sentiments toward specific, personally known others encountered in everyday life—not only general, hypothetical, or one-off rival partisans. In a longitudinal survey experiment, we find that exposure to three brief, scalable treatments over a week reduces partisan animosity, with effects persisting for at least a month. Moreover, the treatments durably ameliorate animosity toward both general outparty members and a personally known outparty member, specified prior to the treatments. These findings suggest promising avenues for redressing social divisions in real-world contexts.